2023
DOI: 10.1021/acs.macromol.3c00941
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Borane Frustrated Lewis Pairs for Metal-Free CO2/Epoxide Copolymerization

Abstract: The development of metal-free catalysts with excellent activity and controllability remains a significant obstacle for the copolymerization of CO2 and epoxides. In this study, we used the frustrated Lewis pair (FLP) composed of commercial tertiary phosphine and trialkylborane to catalyze the copolymerization of CO2 and propylene oxide (PO). The rational matching of the electronic and steric properties of Lewis bases and acids has a great influence on the activity and controllability of CO2 copolymerization. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…The process’s viability depends both on high performance catalysts and on identifying low-energy operating conditions. Both features help to control selectivity since PO and carbon dioxide coupling yield either polymer [PPC or poly­(ether carbonates)] or cyclic carbonate (PC), with the latter generally being the thermodynamic reaction product. There have been some tremendous advances in catalysis, particularly in homogeneous catalysis, with the lead catalysts reaching impressive TOFs (>1000 h –1 ) and polymer selectivity (>99%). , …”
Section: Introductionmentioning
confidence: 99%
“…The process’s viability depends both on high performance catalysts and on identifying low-energy operating conditions. Both features help to control selectivity since PO and carbon dioxide coupling yield either polymer [PPC or poly­(ether carbonates)] or cyclic carbonate (PC), with the latter generally being the thermodynamic reaction product. There have been some tremendous advances in catalysis, particularly in homogeneous catalysis, with the lead catalysts reaching impressive TOFs (>1000 h –1 ) and polymer selectivity (>99%). , …”
Section: Introductionmentioning
confidence: 99%
“…The optimal catalyst Nap-Al 2 with 1,8-naphthalenediol as a rigid skeleton and −O(CH 2 ) 4 O− as a soft linker exhibits outstanding catalytic performance (TOF = 5000 h −1 ) in the ROCOP of CO 2 /PO at 70 °C, outperforming the previously reported PAPC (TOF = 3100 h −1 ) under similar conditions. 32 Moreover, Nap-Al 2 exhibits great thermal stability at a high temperature of 140 °C, achieving a high TOF = 25200 h −1 with a polymer selectivity of 91%. A comprehensive catalytic cycle based on dynamic synergy has been proposed, taking into account the key intermediates involved in the ROCOP of CO 2 /PO.…”
Section: ■ Introductionmentioning
confidence: 99%
“…15 In addition, our previous work clearly indicated that the molecular interactions of aluminum porphyrins were beneficial for boosting the catalytic efficiency. [28][29][30][31][32]44 1a). Moreover, control catalysts with different substitution sites and alkyl chain lengths were also designed (Schemes S4−S8).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The use of organocatalysts, also known as metal-free catalysts, has considerably progressed in organic chemistry since 2000. In polymer chemistry, the ring-opening polymerization of lactide using 4-(dimethylamino)­pyridine as a catalyst was reported in 2002 as the first living polymerization using an organocatalyst . Organocatalytic polymerization has been widely expanded to use applicable cyclic monomers, such as cyclic esters, cyclic carbonates, and epoxides, and copolymerization of epoxide with CO 2 . These new precision polymerization systems require improvement in terms of polymerization activity, chemical selectivity, and polymer structure control. As a different type of polymerization, the group transfer polymerization (GTP) of polar monomers using 1-trimethylsiloxy-1-methoxy-2-methyl-1-propene (silyl ketene acetal, SKA Me ) enables the controlled/living system. Taton et al and Waymouth et al reported that N -heterocyclic carbene efficiently organocatalyzed the GTPs of methyl methacrylate and tert -butyl acrylate and the block GT copolymerization (GTcoP) of n -butyl acylate, N , N -dimethylaminoethyl acrylate, N , N -dimethylaminoethyl methacrylate, N , N -dimethylacrylamide (DMAm), and methacrylonitrile. We have reported that several types of organic molecules categorized as strong Bro̷nsted acids of trifluoromethanesulfonimide (Tf 2 NH) and pentafluorophenylbis­(triflyl)­methane (C 6 F 5 CHTf 2 ), strong Lewis acids of N -(trimethylsilyl)­bis­(trifluoromethanesulfonyl)­imide (Me 3 SiNTf 2 ) and tris­(pentafluorophenyl)­borane (B­(C 6 F 5 ) 3 ), and organic superbases of 1- tert -butyl-4,4,4-tris­(dimethylamino)-2,2-bis­[tris­(dimethylamino)­phosphoranylidenamino]-2Λ5,4Λ5-catenadi­(phosphazene) ( t -Bu-P 4 ) and 2,8,9-triisobutyl-2,5,8,9-tetraaza-1-phosphabicyclo[3.3.3]­undecane (T i BP) have effectively catalyzed the controlled/living GTP of (meth)­acrylate and acrylamide monomers. An optimal organocatalyst/initiator combination is crucial to achieving a controlled/living GTP.…”
Section: Introductionmentioning
confidence: 99%